Streptococcus thermophilus phage monitoring in a cheese factory: Phage characteristics and starter sensitivity - Guglielmotti, Daniela Marta (2009)
Nineteen Streptococcus thermophilus phages isolated from an Argentinean cheese plant were studied regarding their host range, morphology, packaging mechanism and nucleotide sequence of the variable region VR2 (one of the genetic determinants of host specificity). According to their features, they were morphologically classified into Siphoviridae family, morphotype B1. Among the tested phages, 13 distinct restriction patterns were found, and only one phage showed a pac-type mechanism. The classification based on the VR2 sequence demonstrated to be very useful since phages with very different VR2 sequences showed clearly different host ranges.